Phase equilibria of mixtures involving fatty acid ethyl esters and fat alcohols between 4 and 27 kPa for bioproduct production. (15th December 2021) - Roze, Frédéric; Pignat, Patrice; Ferreira, Olga; Pinho, Simão P.; Jaubert, Jean-Noël; Coniglio, Lucie
Graphical abstract: Highlights: New VLE ( PTxyz ) measurements for biolubricants, biofuels, bioplasticizers industries. Data pressure and temperature ranges: 4394–26790 Pa, 306–423 K. Ternary systems studied: [Ethanol + 2-Ethyl-1-hexanol or 1-Octanol + 1-Dodecanol]. Multicomponent system studied: [the ternaries +  Balanites aegyptiaca ethyl esters]. Excellent predictive performance of Dortmund modified UNIFAC model for these VLE. Abstract: The aim of this paper is to bring valuable phase equilibria information for the design and operation of biolubricant and related biofuel product processes. As a result, Vapor-Liquid Equilibrium (VLE) measurements, at different temperatures, pressures and global compositions, for the ternary systems [Ethanol + 2-Ethyl-1-hexanol + 1-Dodecanol] and [Ethanol + 1-Octanol + 1-Dodecanol], as well as a multicomponent system containing these alcohols together with Balanites aegyptiaca fatty acid ethyl esters are reported for the first time (data pressure and temperature ranges: 4394–26790 Pa, 306–423 K). The Dortmund modified UNIFAC model showed very high accuracy in the prediction of these VLE, with overall average absolute deviations on the liquid and vapor molar compositions of 0.007 and 0.0003 for the ternary systems, 0.003 and 0.006 for the multicomponent system.